Komitmen dan Proyeksi Capaian Development Goals Propinsi Sumatera Barat Menyongsong 2015 - Amelia, Dona (Jurnal Ekonomi, 2012)
The Millenium Development's Goals (MDG's) are eight international development goals that were officially established following the millenium summit of the united nations in 2000, following the adoption of the united millenium declaration. All 193 united nations member states and at least 23 international organization have agrees to achieve these goals by the year 2015. To achieve MDG's terget, West Sumatra need to take extra effort because several indicators still take time to achieve MDG's target. It takes 10 years since 2010 to halve poverty rate, 10 years to eradicate illiteracy, 14 years to reach 100% basic education enrollment, 12 years to reduce two third child mortality since 2010, 15 years to reduce two third of mother mortality since 2010, 117 years to free slump dweller, and 7 years to access clean water for houschold since 2010.